Regional unit definition for the nucleus of comet 67P/Churyumov-Gerasimenko on the SHAP7 model. (1st December 2018) - Thomas, N.; El Maarry, M.R.; Theologou, P.; Preusker, F.; Scholten, F.; Jorda, L.; Hviid, S.F.; Marschall, R.; Kührt, E.; Naletto, G.; Sierks, H.; Lamy, P.L.; et al.
Abstract: The previously defined regions on the nucleus of comet 67P/Churyumov-Gerasimenko have been mapped back onto the 3D SHAP7 model of the nucleus (Preusker et al., 2017). The resulting regional definition is therefore self-consistent with boundaries that are well defined in 3 dimensions. The facets belonging to each region are provided as supplementary material. The shape model has then been used to assess inhomogeneity of nucleus surface morphology within individual regions. Several regions show diverse morphology. We propose sub-division of these regions into clearly identifiable units (sub-regions) and a comprehensive table is provided. The surface areas of each sub-region have been computed and statistics based on grouping of unit types are provided. The roughness of each region is also provided in a quantitative manner using a technique derived from computer graphics applications. The quantitative method supports the sub-region definition by showing that differences between sub-regions can be numerically justified. Highlights: Regions are defined upon the latest 3D shape model (SHAP7) of comet 67P/Churyumov-Gerasimenko. The definition is provided in a publicly accessible shape file. Sub-regions of similar properties are defined to support more detailed work. Roughness calculations are performed to quantify differences between regions and sub-regions.